The Ethics That Appear in Miracles 3 - Rungklap, Phra Palat Sitthiphong Thirapunyo; Somchit, Somchay; Khammuangsaen, Boonruam (Journal of Dhamma for Life, 2025)
This research aims to (1) study ethics in the context of Buddhist philosophy, (2) examine the ethical dimensions manifested in miracles according to Theravāda Buddhist philosophy, and (3) analyze the role of miracles as ethical tools that contribute to the moral and intellectual development of individuals. The study emphasizes interpreting miracles as mechanisms for transforming wrong views (micchā-diṭṭhi) into right views (sammā-diṭṭhi), which serve as a foundation for ethical cultivation within the Theravāda tradition. This is qualitative documentary research that gathers data from the Tipiṭaka, its commentaries, and relevant academic literature. The research employs content analysis to synthesize ethical concepts reflected in the three types of miracles: (1) Iddhi-pāṭihāriya (psychic or supernatural powers), (2) Ādesanā-pāṭihāriya (mind-reading or telepathy), and (3) Anusāsanī-pāṭihāriya (miraculous teaching or instruction). The findings reveal that all three types of miracles play a role in communicating and disseminating the Dhamma. However, the Buddha emphasized Anusāsanī-pāṭihāriya as the most ethically significant, as it represents teachings that can be practically applied and lead to profound and sustainable inner transformation. While the other two miracles may possess the power to attract attention, if used without the guidance of wisdom, they may lead to delusion and attachment to miraculous powers rather than a genuine understanding of the Dhamma. In conclusion, ethics in Theravāda Buddhist philosophy prioritizes the use of miracles within the framework of sīla (morality), samādhi (concentration), and paññā (wisdom), aiming to promote genuine ethical development and ultimately liberation from suffering.